Cyprus : Financial Sector Assessment Program; Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses key findings of the Financial System Stability Assessment on Cyprus. The assessment reveals that the banking system of Cyprus has managed to avoid the worst effects of the global financial crisis, but stress tests confirmed that credit risk remains high. The assessment suggests that work on the crisis contingency framework should be completed. Various European Union (EU)-wide and national initiatives are already under way, including strengthening deposit insurance, drafting guidelines for emergency liquidity assistance, and adopting a legal framework for covered bonds to facilitate access to European Central Bank refinancing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet